An Analysis of English Borrowing Words in Indonesian Advertisement “Gatsby Styling Pomade” - Mauliya Avivi; Ramadhani Qonitah Mursyida (Proceedings of The ICECRS, 2020)
This research aims to identify and classify the types of borrowing word in Indonesian advertisement of Gatsby Styling Pomade. Qualitative method is used to analyze and identify the data which consists of borrowing words. The result of this study shows that two types of borrowing word are discovered encompassing loanword and loan shift. There are six words which are discovered as part of borrowing word in this study. Therefore, the most dominant type of borrowing word in this study are both loanword and loan shift.